The Urgency of Protecting the Privacy Rights of Kidfluencers on Social Media in Indonesia in Relation to the 1989 Convention on the Rights of the Child - Asyilla Shafa Aline Faza; Sinta Dewi Rosadi; Betty Rubiati (Fakultas Hukum Dehasen, 2024)
The research aims to analyze the protection of kidfluencers' privacy rights on social media in Indonesia from the perspective of the Convention on the Rights of the Child of 1989 and to analyze the urgency of legal protection for kidfluencers' privacy rights on social media in Indonesia. The approach method used is normative juridical, emphasizing the study of primary, secondary, and tertiary legal materials, as well as a legal comparison between Indonesian law and French law. This study will analyze data obtained from library research using a qualitative juridical analysis method. The results show that the existing laws in Indonesia do not provide adequate protection for kidfluencers' privacy rights on social media. This legal gap has resulted in various cases of privacy rights violations of kidfluencers on social media, indicating the urgency for legal regulations that can provide better protection for kidfluencers' privacy rights.